Recurrence following hemithyroidectomy in patients with low- and intermediate-risk papillary thyroid carcinoma. Issue 6 (5th February 2020) - Ahn, D; Lee, G J; Sohn, J H
Abstract: Background: This study evaluated the incidence, patterns and risk factors for recurrence after hemithyroidectomy in patients with low- and intermediate-risk papillary thyroid carcinoma (PTC), and verified the predictive role of the risk staging systems in current use. Methods: The clinicopathological characteristics and risk categories were analysed according to recurrence in patients who underwent hemithyroidectomy for low- and intermediate-risk conventional PTC, and were followed up for at least 24 months. Five risk staging systems were used to stratify risk: the 2015 American Thyroid Association (ATA) system; Age, Metastases, Extent and Size (AMES) system; Metastases, Age, Complete resection, Invasion and Size (MACIS) system; Grade, Age, Metastases, Extent and Size (GAMES) system; and the eighth AJCC system. Results: The study included 561 patients; 93·9 per cent of the study population (527 of 561) had a papillary thyroid microcarcinoma 1 cm or smaller in size. At a mean follow-up of 83 months, 25 patients (4·5 per cent) had recurrence; among these patients, 23 (92%) presented with a remaining thyroid lobe. Multifocality was significantly associated with recurrence in univariable and multivariable analyses (adjusted hazard ratio 3·16, 95 per cent c.i. 1·25 to 7·98; P  = 0·015). Disease-free survival (DFS) varied according to multifocality ( P  = 0·010). The five risk staging systems were not associated with recurrence, and their Harrell's C-index ranged from 0·500 to 0·531. DFS rates did not differ between the risk categories in each system. Conclusion: Although the recurrence rate after hemithyroidectomy in patients with low- and intermediate-risk PTC was low, meticulous follow-up focusing on the remaining thyroid lobe is needed for early detection and timely management of recurrence. The risk scoring systems in current use have no predictive role in these patients. Graphical Abstract: In this study, the overall recurrence rate after hemithyroidectomy in patients with low- to intermediate-risk papillary thyroid carcinoma was 4·5 per cent (25 of 561), and most recurrences developed in the retained contralateral thyroid lobe. Multifocality was significantly associated with recurrence. However, none of the currently used risk staging systems (2015 American Thyroid Association (ATA); Age, Metastases, Extent and Size (AMES); Metastases, Age, Complete resection, Invasion and Size (MACIS); Grade, Age, Metastases, Extent and Size (GAMES); and 8th AJCC) were associated with recurrence. Recurrence rate low